2010
DOI: 10.1016/j.media.2010.04.007
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput detection of prostate cancer in histological sections using probabilistic pairwise Markov models

Abstract: In this paper we present a high-throughput system for detecting regions of carcinoma of the prostate (CaP) in HSs from radical prostatectomies (RPs) using probabilistic pairwise Markov models (PPMMs), a novel type of Markov random field (MRF). At diagnostic resolution a digitized HS can contain 80K×70K pixels -far too many for current automated Gleason grading algorithms to process. However, grading can be separated into two distinct steps: 1) detecting cancerous regions and 2) then grading these regions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 50 publications
0
121
0
Order By: Relevance
“…Since these methods are automatic, they are not subjective and do not require a time commitment from an individual with pathology expertise. This method has most commonly been applied to assigning a Gleason grade to prostate cancer samples (Doyle et al, 2012b;Monaco et al, 2008;Monaco et al, 2010;Naik et al, 2008Naik et al, , 2007Sparks and Madabhushi, 2013) though it has found applications in other cancers as well (Petushi et al, 2006). The Gleason scoring system is particularly well suited to this type of analysis because the system characterizes how ordered the glands are in a prostate tumor.…”
Section: Image Subsetting Methodsmentioning
confidence: 99%
“…Since these methods are automatic, they are not subjective and do not require a time commitment from an individual with pathology expertise. This method has most commonly been applied to assigning a Gleason grade to prostate cancer samples (Doyle et al, 2012b;Monaco et al, 2008;Monaco et al, 2010;Naik et al, 2008Naik et al, , 2007Sparks and Madabhushi, 2013) though it has found applications in other cancers as well (Petushi et al, 2006). The Gleason scoring system is particularly well suited to this type of analysis because the system characterizes how ordered the glands are in a prostate tumor.…”
Section: Image Subsetting Methodsmentioning
confidence: 99%
“…Given the pathologist's annotation on each image, we manually label 525 artifacts, 931 normal glands and 1,375 cancer glands to form the (ground truth) gland dataset. We also implemented the methods in [2] and [6] to compare them with the proposed method. Since all three methods perform segmentation by starting at the same lumen objects (identified in section 2), and use the same ground truth (which is not affected by lumen objects), the comparison is unbiased.…”
Section: Methodsmentioning
confidence: 99%
“…The average JI value per gland segment obtained by the algorithms in [2], [6] and the proposed NLA algorithm are 0.31, 0.43 and 0.66, respectively. Since the NLA algorithm aims at detecting nuclei surrounding the lumen (while the algorithms in [2] and [6] mostly detect lumen and cytoplasm), it segments more complete gland regions than [2] and [6] (Fig. 2).…”
Section: B Gland Segmentation Evaluationmentioning
confidence: 99%
See 2 more Smart Citations